Thiopurine‐induced mitotic catastrophe in Rad51d‐deficient mammalian cells. (25th September 2017) - Wyatt, Michael D.; Reilly, Nicole M.; Patel, Shikha; Rajesh, Preeti; Schools, Gary P.; Smiraldo, Phillip G.; Pittman, Douglas L.
Abstract : Thiopurines are part of a clinical regimen used for the treatment of autoimmune disorders and childhood acute lymphoblastic leukemia. However, despite these successes, there are also unintended consequences such as therapy‐induced cancer in long‐term survivors. Therefore, a better understanding of cellular responses to thiopurines will lead to improved and personalized treatment strategies. RAD51D is an important component of homologous recombination (HR), and our previous work established that mammalian cells defective for RAD51D are more sensitive to the thiopurine 6‐thioguanine (6TG) and have dramatically increased numbers of multinucleated cells and chromosome instability. 6TG is capable of being incorporated into telomeres, and interestingly, RAD51D contributes to telomere maintenance, although the precise function of RAD51D at the telomeres remains unclear. We sought here to investigate: (1) the activity of RAD51D at telomeres, (2) the contribution of RAD51D to protect against 6TG‐induced telomere damage, and (3) the fates of Rad51d‐ deficient cells following 6TG treatment. These results demonstrate that RAD51D is required for maintaining the telomeric 3′ overhangs. As measured by γ‐H2AX induction and foci formation, 6TG induced DNA damage in Rad51d ‐proficient and Rad51d ‐deficient cells. However, the extent of γ‐H2AX telomere localization following 6TG treatment was higher in Rad51d ‐deficient cells than in Rad51d ‐proficient cells. Using live‐cell imaging of 6TG‐treated Rad51d ‐deficient cells, two predominant forms of mitotic catastrophe were found to contribute to the formation of multinucleated cells, failed division and restitution. Collectively, these findings provide a unique window into the role of the RAD51D HR protein during thiopurine induction of mitotic catastrophe. Environ. Mol. Mutagen. 59:38–48, 2018. © 2017 Wiley Periodicals, Inc.